Representation of Hidden Curriculum in EFL Textbook (Gender Markers) - E. E. Shishlova (MGIMO University Press, 2014)
The article considers the mechanism ofrepresenting the hidden curriculum in the discourse of EFL textbooks, i.e. the transmission ofsociocultural norms and values of native speakers to foreign students. To do this the authors make a brieftheoretical review of this problem and demonstrate the results of the comparative discourse analysis of two popular textbooks, the one of the pre-globalization age and the present-day one. The authors provide evidence for their idea of the dual role, which English plays today being simultaneously a national language of different English-speaking societies and the global lingua franca. The conducted discourse analysis is based on the analysis of semiotic means, which are used to nominate concepts basic to any society and culture. In the article, the authors demonstrate their own plan of analysis by the example of the "gender" concept. The gender concept shows social and cultural conditionality of distinctions in behavior and the identity of men and women. The comparative analysis of gender markers in the discourse of EFL textbooks reveals a global vector of transformation and distribution ofsociocultural values. Authors state that cultural expansion through English teaching is an instrument of smart power. It is suggested using the mechanism of transmission ofsociocultural norms and values, which is analyzed in the research, to create Russian textbooks for foreign students.